Stilbenes as κ-Selective, Non-nitrogenous Opioid Receptor Antagonists - Hartung, Alyssa M. (American Chemical Society and American Society of Pharmacognosy, 2014)
[Image: see text] The natural stilbene pawhuskin A has been shown to function as an opioid receptor antagonist, with preferential binding to the κ receptor. This finding encouraged assembly of a set of analogues to probe the importance of key structural features. Assays on these compounds determined that one (compound 29) shows potent opioid receptor binding activity and significantly improved selectivity for the κ receptor. These studies begin to illuminate the structural features of these non-nitrogenous opioid receptor antagonists that are required for activity.